Electronic voting and public spending: The impact of de facto enfranchisement on federal budget amendments in Brazil - Rodrigo Schneider; Diloá Athias; Mauricio Soares Bugarin (Journal of Applied Economics, 2020)
This article examines whether an increase in political participation biased toward low-income voters - and concentrated in legislative elections - impacts federal representatives' allocation of resources from the federal budget to Brazilian municipalities. We use a regression discontinuity design that exploits the assignment of electronic voting to municipalities based on population size to identify the causal effect of enfranchisement on the allocation of federal public spending. We find that an increase of 1 percentage point in the valid-vote-to-turnout ratio for federal representatives in a municipality increases the allocation of funds from the federal budget by 3.3%, and that experienced politicians are more responsive to the enfranchisement of low-income voters.
Keywords: 330; Electronic voting; political participation; politically motivated transfers